Valid publication for 101 species and subspecies names of the genera Nasa and Aosa (Loasaceae: Cornales) - Weigend, Maximilian (2006)
In the present paper, the valid names of 101 taxa of new species, new subspecies and new combinations of the genera Nasa and Aosa (Loasaceae: Cornales) are published. The invalid names of these taxa were originally published in various articles in the last ten years. This publication is carried out on the basis of the changes in the International Code of Botanical Nomenclature approved in the International Botanical Congress (IBC) in Viena, 2005. For each taxon the valid names, protologue citation and type are provided, in the case of the 41 new species and subspecies a latin diagnosis is included, as per requirement ot the Code. We additionally provide the citation for the original, invalid publication and corresponding illustration of the taxon. The taxon list here provided represents a complete list of all taxa currently known in the genus Nasa, including the species recently validated in TAXON.